MARKETING STRATEGIES FOR TOURISM VILLAGE IN WEST BANDUNG DISTRICT IN COVID-19 PANDEMIC - Sianipar, Rosianna; Juliana, Juliana; Sitorus, Nova Bernedeta (Journal of Industrial Engineering & Management Research, 2022)
Marketing strategy is a plan that is carried out to capture the market, using the 8 Ps Marketing Mix strategy. The research objective is to analyze marketing strategies, internal and external factors for developing tourist villages in West Bandung Regency which can increase tourist visits. The sample used in the study used purposive sampling. This study uses a qualitative approach. The analysis used in this study uses a SWOT analysis. By implementing the 8 Ps marketing mix, the marketing strategies that can be applied include improving facilities and accessibility to Suntenjaya Village. Improve facilities and accessibility to Cihanjuang Rahayu Village. During the COVID-19 pandemic, products can be made in the form of virtual tours so that people can still enjoy them. The study results found that marketing strategy was done through several social media such as Facebook, Instagram and Tiktok that can be used according to the age segment of tourists. can be enjoyed by tourists which can be done online, make natural and cultural tour packages in each village, carry out cooperation with the campus by providing training related to tourism and hospitality in order to provide excellent service in tourist villages. Communities who take part in tourism management in the village are given training related to their expertise so that they can provide excellent service for tourists. Careful planning and marketing can reduce the harmful effects of tourism development.